Form, functions and meaning of Malay Tepak Sirih in Malaysia / Siti Hajar Maizan - Maizan, Siti Hajar (2015)
Tepak sirih is one of the objects of the cultural heritage of the Malays that are still being used as a medium during a ceremony among the Malay community including proposing, engagement and marriage, as well as used, in official and royal ceremonies. Aim of this research is to study the form, function and meaning of Malay tepak sirih in Malaysia using theory by Meyer Schapiro (1953). This research started with describing the form and function form each tepak sirih that been studied.Samples were collected from six different museums in Kuala Lumpur and Melaka. To gain better understanding, interview with the curators and academician were conducted. The result of this study showed that tepak sirih has varieties of forms and motifs such as floral and fauna elements were significantly found at most of the Malay tepak sirih designs and rectangular-shaped. It has been used in official ceremonies such as meeting Sultan and unofficial ceremonies such as starting a conversation during proposing or engagement event. The meanings for each tepak sirih are different and most of it are related with the Malay philosophy. However, the modernization has transferred the design of tepak sirih to a very simple form and decoration, which are more minimal and plain. Finally, from the study concluded that Malay tepak sirih need to be preserved in term of the form, function and meaning so as retaining the customs and tradition of Malay sense could keep the traditional things like tepak sirih can be sustained and valued by the future generation. Other than that,Malay community by not only follows the tradition but the appreciation and an interpretation for the tepak sirih that can be practice today.